Case report: Second report of neuromuscular syndrome caused by biallelic variants in ASCC3 - Li, Wang; Li, Zhongliang; Fu, Junhui; Xu, Kaili; Mei, Daoqi; Wang, Xiaona; Li, Taisong; Du, Xilong (Frontiers in Genetics, 2024)
Activating Signal Cointegrator 1 Complex, Subunit 3 (ASCC3) has been implicated in the pathogenesis of neurodevelopmental disorders and neuromuscular diseases (MIM: 620700). This paper analyzes the clinical manifestations of three patients with developmental delay caused by ASCC3 genetic variation. Additionally, we discuss the previously reported clinical features of these patients along with our own findings, thereby enhancing our understanding of these genetic disorders and providing valuable insights into diagnosis, treatment, and potential interventions for affected individuals. Methods: In this study, we utilized trio-whole-exome sequencing (Trio-WES) and trio-copy number variations sequencing (Trio-CNV-seq) to analyze three unique families diagnosed with developmental delay caused by variation in ASCC3. Additionally, we retrospectively examined eleven previously reported ASCC3 genetic variations exhibiting similar clinical features.Results: Proband Ⅰ (family 1) and Proband Ⅲ (family 3) exhibited global developmental delays, characterized by intellectual disability, motor impairment, language retardation, lower muscle strength, and reduced muscle tone in their extremities. Proband Ⅱ (family 2) presented poor response and dysphagia during feeding within seven days after birth, clinical examination displayed short limbs, long trunk proportions, and clenched fists frequently observed alongside high muscle tone in his limbs -all indicative signs of developmental delay. Trio-WES revealed compound heterozygous variants in ASCC3 inherited from their parents. Proband Ⅰ carried c.[489 dup];[1897C>T], proband Ⅱ carried c.[2314C>T];[5002T>A], and proband Ⅲ carried c.[5113G>T];[718delG ] variations, respectively.Conclusion: This study present the first report of Chinese children carrying compound heterozygous genetic variants in ASCC3 with LOF variants, elucidating the relationship between these variants and various aspects of intellectual disability. This novel finding expands the existing spectrum of ASCC3 variations.